Flexible Control of Photovoltaic Grid-Connected Cascaded H-Bridge Converters during Unbalanced Voltage Sags - Dehghani Tafti, Hossein (2018)
Multilevel cascade H-bridge (CHB) converters are one of the promising solutions for medium- and large-scale grid-connected photovoltaic power plants. However, there is a lack of a complete study about their operation during voltage sags. This paper proposes a flexible control strategy for the operation of photovoltaic grid-connected CHB inverters during unbalanced voltage sags. The key novelty is that the proposed strategy is able to inject both active and reactive powers to the grid with either balanced or unbalanced currents, while ensuring that all dc-link capacitor voltages remain balanced. The simulation and experimental evaluations of a 9-kVA grid-connected seven-level CHB illustrate and validate the performance of the proposed strategy for the operation of the grid-connected CHB converter during different unbalanced voltage sags.